Design of Arm Processor’s Elements Using QCA - Asthana, Amita; Anil Kumar, Dr.; Preeta Sharan, Dr.; Sumita Mishra, Dr. (International Journal of Engineering and Technology, 2018)
Quantum dot Cellular Automata is one of the promising future nano-technology for transistor-less computing which takes advantage of the coulomb force interacting between electrons. The aim of this paper is to consider the logical circuits of ARM processors and further reducing their size in nanometres like 2:1 multiplexer , D Flip Flop, scan Flip Flop, 2:1 multiplexer with enable, encoder, decoder, SR FF, shift register, memory cell and program counter are designedÂ using QCAD tool . Their cell count, area, kink energy are taken in consideration to calculate power and energy dissipation.Â Â